A Low‐Temperature Additive‐Involved Leaching Method for Highly Efficient Inorganic Perovskite Solar Cells. Issue 1 (16th November 2020) - Sun, Xiuhong; Shao, Zhipeng; Rao, Yi; Meng, Hongguang; Gao, Caiyun; Chen, Chen; Liu, Dachang; Lv, Peiliang; Li, Zhipeng; Wang, Xiao; Cui, Guanglei; Pang, Shuping
Abstract: Inorganic CsPbI3 perovskite with an optical bandgap ranging from 1.67 to 1.75 eV is a promising light‐harvesting material as a top cell in tandem solar cells, but its high fabrication temperature can damage the middle layers or the bottom subcells. Here, an additive‐involved leaching method to fabricate CsPbI3 perovskite films is demonstrated, which can decrease the preparation temperature to 100 °C. The CsPbI3 perovskite films with high crystallinity are achieved by a solution assisted reaction between DMAPbI3 and Cs4 PbI6 with the leaching of DMA +, Cs +, and I − . The as‐prepared CsPbI3 perovskite films exhibit much superior stability compared to their high‐temperature counterparts. As a result, a power conversion efficiency of over 16% is obtained, and the unencapsulated device maintains over 93% of the initial efficiency after aging for 30 days in air with a relative humidity of 10%. Abstract : An additive‐involved leaching method is proposed to reduce the preparation temperature of CsPbI3 to 100 °C. The CsPbI3 perovskite film with high crystallinity is formed by an ion exchange reaction between DMAPbI3 and Cs4 PbI6 . More than 16% photoelectric conversion efficiency can be achieved and the inencapsulation device exhibits remaekable stability.